Precision public health after Covid-19: a scoping review - Martha Kenney; Laura Mamo (International Journal for Equity in Health)
Abstract “Precision public health” (PPH) emerged in 2015 as a charismatic vision to revolutionize traditional public health with data-driven solutions to the world’s most challenging public health problems. A central goal of PPH is to use population-level data to improve health equity by targeting geographically localized at-risk populations. For this article, we conducted a scoping review to investigate whether and how PPH approaches were used for Covid-19 pandemic response and how they incorporated health equity goals in their approaches. We found that during the Covid-19 pandemic, discussions of PPH in the academic literature mostly focused on potential future implementation of PPH rather than on-the-ground Covid-19 pandemic response. In the few articles that described a research project and/or public health intervention at the intersection of PPH and Covid-19, researchers articulated PPH together with three sets of Covid-19 era public health practices: 1) vulnerability indexes; 2) near real-time surveillance; 3) pathogen sequencing. In each of these articulations, the most common method for achieving health equity was using epidemiological surveillance data to create risk stratification to direct resources to the most vulnerable. As these new articulations are tentative and have not yet become common in public health literature and policy, the article ends with a critical call to interrogate which versions of health equity are enacted and foreclosed in data-driven approaches to public health and how PPH can best serve vulnerable populations.